2014
DOI: 10.1016/j.chaos.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Least squares shadowing sensitivity analysis of a modified Kuramoto–Sivashinsky equation

Abstract: Computational methods for sensitivity analysis are invaluable tools for scientists and engineers investigating a wide range of physical phenomena. However, many of these methods fail when applied to chaotic systems, such as the Kuramoto-Sivashinsky (K-S) equation, which models a number of different chaotic systems found in nature. The following paper discusses the application of a new sensitivity analysis method developed by the authors to a modified K-S equation. We find that least squares shadowing sensitivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 18 publications
4
63
0
Order By: Relevance
“…The cause of the discrepancy between gradients from LSS and curve fitting is discussed by the authors in their analysis of LSS applied to the K-S equation. 14 We found that the systematic error arises from breaks in the assumption of ergodicity. The convergence of LSS to the true gradient value can be proven if the system is ergodic for all initial conditions.…”
Section: Error In Lss Due To Breaks Of Ergodicitymentioning
confidence: 98%
See 4 more Smart Citations
“…The cause of the discrepancy between gradients from LSS and curve fitting is discussed by the authors in their analysis of LSS applied to the K-S equation. 14 We found that the systematic error arises from breaks in the assumption of ergodicity. The convergence of LSS to the true gradient value can be proven if the system is ergodic for all initial conditions.…”
Section: Error In Lss Due To Breaks Of Ergodicitymentioning
confidence: 98%
“…The behavior exhibited by both equations has similarities to the behavior observed for large scale turbulent fluid flows. 10,14 Because of this, it is important to understand the source of the systematic error in gradient observed for both systems and determine how to mitigate it, so that LSS may be extended to turbulent fluid flows of interest to aerospace engineers. Figure 2 shows gradients computed using LSS and curve fitting for the K-S equation and Lorenz 96 system.…”
Section: Error In Lss Due To Breaks Of Ergodicitymentioning
confidence: 99%
See 3 more Smart Citations